Current Knowledge of Hepatitis E Virus (HEV) Epidemiology in Ruminants - Federica Di Profio; Vittorio Sarchese; Andrea Palombieri; Paola Fruci; Gianvito Lanave; Serena Robetto; Vito Martella; Barbara Di Martino (Pathogens, 2022)
Hepatitis E virus (HEV) infection represents an emerging public health concern worldwide. In industrialized countries, increasing numbers of autochthonous cases of human HEV infection are caused by zoonotic transmission of genotypes 3 and 4, mainly through the consumption of contaminated raw or undercooked meat of infected pigs and wild boars, which are considered the main reservoirs of HEV. However, in the last few years, accumulating evidence seems to indicate that several other animals, including different ruminant species, may harbor HEV. Understanding the impact of HEV infection in ruminants and identifying the risk factors affecting transmission among animals and to humans is critical in order to determine their role in the epidemiological cycle of HEV. In this review, we provide a summary of current knowledge on HEV ecology in ruminants. A growing body of evidence has revealed that these animal species may be potential important hosts of HEV, raising concerns about the possible implications for public health.